Congenital absence of pericardium - Rahul Nikam; Jordan Rapp; Ashrith Kandula; Snigdha Puram; David Saul (Wolters Kluwer Medknow Publications, 2020)
A 16-year-old girl presented to the emergency department with orthopnea and exercise intolerance for 1 week. Electrocardiogram at that time showed rightward deviation of the cardiac axis, with nonspecific T-wave inversion in the lateral precordial leads and flattening in the inferior leads. She was discharged from the emergency department with cardiology follow-up. Subsequent echocardiogram demonstrated that "the heart is in a funny position in the chest," and computed tomography of the chest was requested to evaluate for a mediastinal mass causing leftward displacement of the heart.